Retrospective analysis of interferon-alfa, interleukin-2 and 5-fluorouracyl based chemioimmunotherapy in treatment of patients with metastatic renac cell carcinoma - Obrocka, Beata; Szczylik, Cezary; Żołnierek, Jakub; Korniluk, Jan; Leśniewski-Kmak, Krzysztof; Nurzyński, Paweł (Contemporary Oncology/Współczesna Onkologia, 2005)
The role of immunotherapy based on interferon-alfa and interleukin-2 in treatment of patients with metastatic renal cell carcinoma is unclear and its impact on survival is still controversial. The retrospective evaluation of safety and efficacy of combined chemioimmunotherapy based on these cytokines was performed in CSK MON WIM Oncology Clinic in Warsaw. Between February 2003 and April 2003 seventy seven nephrectomised patients aged 23-76 years old in good performance status and with adequate organ function were treated with investigational regimen. The aim of the analysis was to assess the tolerance of the treatment, overall response rate, overall survival, time to progression and selection of prognostic and predictive factors for survival and objective response respectively. In general observed toxicity was mild to moderate and mainly consisted of symptoms and signs of flu-like syndrome (CTC grade 1-2). Although about 43% of patients experienced CTC grade 3 side effects and one person CTC grade 4 fever, severe toxicity tended to occur just after beginning of the therapy and was easily manageable with standard supportive care. The objective responses were observed in twenty patients (25.9%): 6 complete remissions (7.8%) and partial (16.8%). Median time of complete remission was assessed to be 22.6 months, median time of partial response – 13.6 months. Median time to progression was equal to 12.5 months. Overall survival time ranged between 3.8 and 48.6 months where median survival was 19.9 months. Prognostic and predictive factors were identified and appropriate Cox’s models were constructed.